Designing a Switching Controller Based on Control Performance Assessment Index and a Fuzzy Supervisor for Perturbed Discrete-Time Systems Subject to Uncertainty - Mohammad Babaie; Rahmani, Zahra; Rezaie, Behrooz (Automatic control and computer sciences, 2019)
In this paper, a switching control strategy based on control performance assessment index namely Harris index and a fuzzy supervisor has been proposed for a perturbed discrete-time system subject to uncertainty. In the switching strategy, multiple controllers are utilized so that their virtues such as robustness, minimum output variance and minimum domain of control effort have been achieved simultaneously. Disadvantages of the used controllers like chattering and sensitivity to uncertainty are also improved. The Switching strategy has been designed in three steps. First of all, proper controllers have been designed which are minimum variance, incremental minimum variance and quasi sliding mode controllers. Then, Harris index and fuzzy supervisor are also designed in the next steps respectively. The Harris index has been determined to select proper controller among the available controllers for regulatory and tracking problems. The fuzzy supervisor is also designed to improve Harris index performance. The fuzzy supervisor is Sugeno type which can be used as a supervisor on Harris index operation, especially in presence of uncertainties. Finally, simulation results show that proposed control strategy improves the output variance effectively, reduces chattering domain of control input and sensitivity to uncertainty.